Aspiration pneumonia in a mentally handicapped patient due to a foreign body impacted in the pharynx: a near fatal outcome. Issue 4 (July 1996) - Asgarali, S; Nandapalan, V; Phillips, D; Osunuga, O
Abstract : A case is reported of a mentally handicapped women with dysphagia caused by a foreign body impacted in the pharynx. The case illustrates a potential pitfall in the management of patients who are unable to communicate either verbally or in writing and who present with acute dysphagia.